Rock Properties Determined Continuously from TBM Excavation Process - Edita Lazarová; Víťazoslav Krúpa (Acta Montanistica Slovaca, 2004)
The computer monitoring system used at excavation of exploratory galleries of motorway tunnels Branisko and Viòové-Dubná skala (excavated by Wirth TB-II-330H/M and Voest Alpine ATB 35H, respectively) brought an ample study material. Several characteristics of rock environment in the line of exploratory galleries were determined using developed mathematical models. The verification of the models was carried out based on the comparison of results of mathematical models with results of common procedures of detailed engineering-geological investigation. The description of the continuous method and the results of comparisons are subject of this paper.